DARE Newsletter, Vol. 17, Nos. 2/3, Spring/Summer 2014 - Clark, Amy; Hall, Joan Houston; Stark, Detlef; DARE (Dictionary of American Regional English, 2014)
Contents: "Georgia (Still) on My Mind (Part 1)" by Detlef Stark; "Chief Editor's Funding Update" by Joan Houston Hall; "Digital DARE Quiz Winner"; " 'Do You Speak Wisconsin?' Online Survey Extended"; "A Postscript on Plog(ged)"; "DARE Essay Contest Winner: 'DARE to Dream' " by Amy Clark; "DARE Staff Departures"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States